2022
DOI: 10.3390/tropicalmed7070130
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on COVID-19 Vaccine Hesitancy in sub-Saharan Africa

Abstract: Rates of vaccination against COVID-19 remain lower in sub-Saharan Africa than in other low and middle-income regions. This is, in part, attributed to vaccine hesitancy, mainly due to misinformation about vaccine origin, efficacy and safety. From August to December 2021, we gathered the latest experiences and opinions on four vaccine hesitancy-related areas (policies, perceived risk religious beliefs, and misinformation) from 12 sub-Saharan African researchers, four of whom have published about COVID-19 vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 9 publications
5
44
0
Order By: Relevance
“…This points to the need to educate females regarding the need for vaccines. Furthermore, religious influence in vaccination has been observed since Christians have a higher likelihood of taking the vaccine, which is in congruence with a review of 12 Sub-Saharan African countries, including Ghana, which also stated that vaccine hesitancy has been due to religious beliefs, which could be overcome through communication strategies by addressing the concerns of community [31]. We observed that there were higher odds of taking the first shot of the vaccine among participants with three years of experience, which is consistent with the findings of a study that reported that occupation influenced the acceptance of the COVID-19 vaccine in Ghana [32].…”
Section: Discussionsupporting
confidence: 74%
“…This points to the need to educate females regarding the need for vaccines. Furthermore, religious influence in vaccination has been observed since Christians have a higher likelihood of taking the vaccine, which is in congruence with a review of 12 Sub-Saharan African countries, including Ghana, which also stated that vaccine hesitancy has been due to religious beliefs, which could be overcome through communication strategies by addressing the concerns of community [31]. We observed that there were higher odds of taking the first shot of the vaccine among participants with three years of experience, which is consistent with the findings of a study that reported that occupation influenced the acceptance of the COVID-19 vaccine in Ghana [32].…”
Section: Discussionsupporting
confidence: 74%
“…We observed that Kweneng district with negative sentiment hotspot is predominantly Christians and the second highest populated district. This could also suggest that religion may have played a major role in influencing citizens' sentiments against vaccination, given that a lot of religious leaders were against the vaccine mandate at that time [10]. Further, the combination of all the locations identified with neutral sentiment hotspots and the Kweneng district identified with the negative sentiment hotspot amounted to about 35% of the countries total population.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some conspiracy theorists had rumoured that the COVID-19 vaccination mandate is targeted to depopulate Africa. While some religious leaders and influencers advised their followers against taking the COVID-19 vaccines [3], [10]. Others took to legal action against the compulsory vaccination of citizens, they argued that it is against the citizens' fundamental human right [11].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the findings from this study, however, much needs to be done at better educate the population on subjects relating to the Covid-19 vaccines. In addition, with the protracted history of vaccine hesitancy in Northern Nigeria [19,20], and the gross disconnect between political leaders and the citizens, the Government of Nigeria needs to do more in a bid to ease this strained relationship between the leaderships and their followers. Neglecting the place of trust in governance could also account for vaccine apathy as currently being witnessed with the Covid-19 vaccine hesitancy in Northern Nigeria [21].…”
Section: Discussionmentioning
confidence: 99%